PARTISIPASI PENGUNJUNG TERHADAP KAWASAN EKOWISATA TAMAN WISATA MANGROVE KLAWALU KOTA SORONG - Burmanus Alfons; Yerrynaldo Loppies (SOSCIED, 2026)
This study aims to analyze the level visitor participation in the management of the Klawalu Mengrove Tourism  Area in the Sorong City. This Study Used Quantitaive methods, Collecting 60 Respondents through Questionnaires distributed to visitors.The result of the study showed that caharacteristic of respondents with the gender that had the largest were women at 57 % (34 people). The age of the respondents was the 18-24 years age group at 62% (37 people), fo the caharateristic of high school/vocation school education level with a percentage of 30 % (18 people) an the frequency of visits had the highest  number of visit 2-25 times with a percetange of 47%(28 people). While the resultsof the 5 statement indicatiors, respondent gave a positive answer of 36 respondents who they agreed, Mangrove Diversity gave a posistive answer of 33respondens who stated they strongly agredd, knowledge abiut mangrove gave a possitive  answer of 40 respondent who the stated they strongly agred, mangrove forest area faclilties gave answer 20 respondents who stated they strongly aggred, statisfaction gave a positive answer of 38 respondents  who stated they agredd with visting the mangrove forest area.